Study on Calculation Models of Earth-Air Heat Exchanger Systems. (3rd September 2014) - Bisoniya, Trilok Singh; Kumar, Anil; Baredar, Prashant
Abstract : Modeling is very useful tool in order to predict the effect of the operating parameters like pipe length, radius, depth of burial and air flow rate on the thermal performance and heating/cooling capacity of earth-air heat exchanger (EAHE) systems. Till date many researchers have carried out a number of studies on calculation models for earth-air heat exchanger systems. The analysis of EAHE systems started with the development of one-dimensional models. The two-dimensional models came into practice during the 1990s and were replaced by three-dimensional models in recent years. Latest models are dynamic and technically more advanced which can provide room for all types of grid geometry to produce detailed thermal analysis of EAHE systems. This paper reviews on calculation models of EAHE systems as of the end of March, 2014.